Safety, tolerance, and pharmacokinetics of salvianolic acid B in healthy Chinese volunteers: A randomized, double-blind, placebo-controlled phase 1 clinical trial - Cheng, Junlin; Long, Jun; Zhang, Jingjing; Han, Le; Hu, Yunfang; Liu, Jianghui; Qiu, Runze; Zhu, Zhibin; Fan, Hongwei (Frontiers in Pharmacology, 2023)
Background: Salvianolic acid B is one of the main active ingredients of salvia miltiorrhiza Bunge. In China many Traditional Chinese Medicines have been modified into injections for higher bioavailability and better efficacy. Salvianolic acid injection has been widely used in clinic. Objective: This phase 1, randomized, double-blind, placebo-controlled, single-center study aimed to evaluate the safety, tolerance, and pharmacokinetics of Sal B injection in Chinese healthy volunteers. Methods: For the single-ascending-dose study, forty-seven healthy volunteers were randomly divided into 25, 75, 150, 200, 250 and 300 mg groups. For the multiple-ascending-dose study, sixteen healthy volunteers were randomly divided into 150 and 300mg groups. In each group volunteers were treated with Sal B or placebo randomly. The safety was evaluated by skin test, physical examination, vital sign, laboratory examination, 12 lead electrocardiogram, Holter and clinical symptom and sign. Blood sample were collected in 75, 150, 300 mg single-ascending-dose study groups and 150 mg multiple-ascending-dose study group to determine concentration of salvianolic acid B. Results: In single-ascending-dose study groups there were 41 adverse events in 24 cases (51.1%, 24/47). In multiple-ascending-dose study groups there were 13 adverse events in 8 cases (50.0%, 8/16). Sixty-six volunteers received skin test and three of them were excluded for positive result. adverse events related to the treatment included increased alanine aminotransferase (4.0%), increased bilirubin (2.0%), increased creatinine kinase-MB (2.0%), increased brain natriuretic peptide (8.0%), increased urine N-acetyl-β-D-glucosidase (4.0%), dizziness (2.0%) and chest discomfort (2.0%). No serious adverse events occurred. No volunteers withdrew from the trial. Peak plasma concentration and area under the plasma concentration-time curve of salvianolic acid B progressively increased in a dose-dependent manner in 75, 150 and 300 mg single-ascending-dose study groups. There was no accumulation after consecutive five days administration of 150 mg salvianolic acid B. Conclusions: Salvianolic acid B injection administered up to 300 mg in single dose and 250 mg for consecutive five days showed excellent safety and tolerability in Chinese healthy volunteers. Clinical Trial Registration: www.chinadrugtrials.org.cn, identifier CTR20192236.